THE INFLUENCE OF INFLATION, GOVERNMENT SPENDING AND UNEMPLOYMENT RATE ON ECONOMIC GROWTH IN INDONESIA, 2001-2021(PUBLIC SECTOR CASE STUDY) - Reza Juanda (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to examine the effect of inflation, government spending, and the unemployment rate on economic growth in Indonesia. The data used in this research is secondary data. The population in this study was 34 provinces using a saturated sample technique. The data analysis method in this study uses multiple linear regression analysis with panel data. The results showed that partial inflation and government spending had a positive and significant effect on economic growth in Indonesia, while the unemployment rate had a negative and significant effect on economic growth in Indonesia. Simultaneously inflation, government spending, and the unemployment rate had a positive and significant effect on economic growth in Indonesia.